The Subjective Implications of Bioethics and Education in the Process of Human Formation (Revista Iberoamericana de Bioética, 2025)
This article analyzes the objective and subjective losses of students as a result of the pandemic—based on data presented by UNICEF—between the years 2020 and 2022. The interdisciplinary approach supported by Hossne (2009), Schramm (2006), Gentili (2009), Quijano (2005) and Morin (2002, 2011, 2015), expresses the theoretical contribution with document analysis procedures and narrative review. The article highlights the need for human formation and the recognition of the development of technology to face a fragile world due to the emergency that put human dignity at risk. The text is organized into four parts: (i) the theme; (ii) a contextualization of formal education in the context of a pandemic; (iii) a discussion of subjective education data; and finally, (iv) reflections on the role of the school in the subjective aspects of human development.
Keywords: bioethics; education; human formation; fragilities; pandemic